In vitro/in vivo performance of different complexes of itraconazole used in the treatment of vaginal candidiasis - Mohammad Aamir Mirza; Mohammad Akhlaquer Rahman; Sushama Talegaonkar; Zeenat Iqbal (Universidade de São Paulo, 2012)
A large majority of new chemical entities and many existing drug molecules exhibit poor aqueous solubility, which may limit their potential use in developing drug formulations, with optimum bioavailability. One of the approaches to improve the solubility of a poorly water soluble drug and eventually its bioavailability is complexation with agents like humic acid (HA), fulvic acid (FA), β-cyclodextrin (β-CD), 2-hydroxypropyl-β-cyclodextrin (HP-β-CD) and caffeine (Caff). The current work emphasized at employing these agents to prepare different complexes and their in vitro/in vivo assessment. All the complexes evaluated for their complexation efficiency and authenticated by molecular modeling; conformational analysis, differential scanning calorimetry (DSC), X-ray diffraction (XRD), nuclear magnetic resonance (NMR) and mass spectroscopy. Furthermore, the complexes were assessed in an in vivo, rat vaginal model for their efficacy in treatment of vaginal candidiasis. Amongst the five tested complexes, fulvic acid-itraconazole complex yielded better solubility as well as in vivo efficacy and therefore may further be explored for developing a commercial formulation for treating vaginal candidiasis. A maioria das novas entidades químicas e muitas moléculas de fármacos existentes apresenta fraca solubilidade em água, o que pode limitar seu uso potencial no desenvolvimento de formulações com biodisponibilidade ideal. Uma das abordagens para melhorar a solubilidade de um fármaco pouco solúvel em água e, eventualmente, a sua biodisponibilidade é a complexação com agentes como o ácido húmico (HA), ácido fúlvico (FA), β-ciclodextrina (β-CD), 2-hidroxipropil-β-ciclodextrina (HP-β-CD) e cafeína (Caff). O presente trabalho baseia-se no uso desses agentes para preparar diferentes complexos e suas avaliações in vitro/in vivo. Todos os complexos foram avaliados quanto à eficiência de complexação por modelação molecular, análise conformacional, calorimetria de varredura diferencial (DSC), difração de raios-X (XRD), ressonância magnética nuclear (RMN) e espectroscopia de massas. Além disso, os complexos foram avaliados in vivo, em ratas, no tocante à sua eficácia no tratamento de candidíase vaginal. Entre os cinco complexos testados, o complexo de ácido fúlvico-itraconazol foi o que apresentou melhor solubilidade, bem como melhor eficácia in vivo e, portanto, pode ser explorado para o desenvolvimento de uma formulação comercial para o tratamento de candidíase vaginal.